ASSESSMENT OF THE IMPEDIMENTS TO ACHIEVING EFFECTIVE AND OPTIMUM FIRE PREVENTION AND CONTROL - ABUBAKAR ALKALI, IBRAHIM (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
Markets are complex entities comprising of multiple units ranging from economic, socio cultural, infrastructural, technological and environmental viewpoints. Therefore, its designs especially with regards to fire prevention and control goes beyond active and passive fire prevention and control measures. There are non-salient issues that are usually given less attention but has great impact on the causes as well as hinder the control of market fires. Through qualitative approach involving observation, this study explored three major markets in Kano city using purposive sampling with a view to identifying the challenges of those markets in achieving the optimum fire prevention and control required for such commercial enterprise. The study found alterations, congestion, clearance, extension, indiscriminate parking, squatter trading, hawking/peddling and poor circulation as a challenge to optimum fire prevention and control in the markets. Negligence to the fire prevention and control strategies observed in the markets are believed to have high tendency exacerbating fire disasters with little or no chances of control and evacuation. It is thus imperative to have proactive measures that will enforce the existing development control regulations, fire prevention and control act and ensure orderliness in the market. In addition there is dire need for customized design framework that is conscious of the peculiarities of market settings and operations of such study areas and alike.